42=z/8+39

Simple and best practice solution for 42=z/8+39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42=z/8+39 equation:



42=z/8+39
We move all terms to the left:
42-(z/8+39)=0
We get rid of parentheses
-z/8-39+42=0
We multiply all the terms by the denominator
-z-39*8+42*8=0
We add all the numbers together, and all the variables
-1z+24=0
We move all terms containing z to the left, all other terms to the right
-z=-24
z=-24/-1
z=+24

See similar equations:

| 3(x+5)=1+5x | | 3x+15=1+5x | | 2z-74=24 | | 1x=6=2x | | c/4+8=12 | | 1x+6=50.50 | | 3u+7=-3u+5 | | 3x+1=x-15 | | 1x=5=-7 | | x2-1=80 | | 175m-75+48,250=51,000-15 | | -4y=-5y+3 | | 18=2g=4g | | 3u-2=-2=3u | | 4(2x-1)=-6(x+8)=-3 | | -4s+10=10-4s | | (2x+5)9x-1)=12x | | -10m+10m=0 | | 20x^2-12-8x=49x-52 | | -9r+9r=0 | | -1+8r=3+8r | | -1+8r=3 | | -3d=1-3d | | 4x+27=9x+8=180 | | 14=u/4-9 | | 2x+4=5(x-1)-3(x+2) | | 2(-3c+4)=20 | | 5x+-2(-3+x)=0 | | |2b+17|=-13 | | -7c-1=9-7c | | 8b+b=9b | | 1/4p+3=p+8 |

Equations solver categories